EKSPOR INDONESIA DALAM 2 DEKADE DAN FAKTOR-FAKTOR YANG MEMPENGARUHI - Murdo, Ilham Tri; Affan, Junaidi (Program Studi Manajemen, 2022)
This study is to determine the extent to which the independent variable factors (GDP, Inflation, Exchange and Interest Rates) affect the dependent variable (Exports) in the last 20 years. Quantitative research aims to obtain empirical evidence regarding the effect of the variables of GDP, Inflation, Exchange Rates and Interest Rates on Exports, and also to test hypotheses in order to strengthen or even reject the hypothesis. With the following results: Gross Domestic Product (GDP) has a positive and significant effect on exports, Inflation has no effect on exports, Exchange rates have a negative and significant effect on exports, Interest Rates have no effect on exports, Gross Domestic Product (GDP), Inflation, Exchange rates and interest rates simultaneously and significantly affect exports